2001
DOI: 10.1139/cjz-79-4-554
|View full text |Cite
|
Sign up to set email alerts
|

Population variation in the metabolic response of deer mice to infection with <i>Capillaria</i> <i>hepatica</i> (Nematoda)

Abstract: The effects of parasites on their hosts can vary among host populations, but few studies have examined geographic variation in host-parasite interactions. We examined the effects of Capillaria hepatica (Nematoda) infection on deer mice (Peromyscus maniculatus gracilis) from two different populations. Specifically, we measured the basal metabolic rate (BMR), cold-stress maximum oxygen consumption (MR peak ), metabolic scope (MR peak /BMR), and thermogenic endurance of infected and uninfected mice from one popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…However, we did not detect an interactive effect of thermoregulation and pathogen infection on metabolic rate, indicating that the energetic costs of infection with M. gallisepticum are comparable at thermoneutral and subthermoneutral temperatures. Our results are consistent with previous work in endothermic rodents, which detected additive but not interactive effects of cold exposure and nematode parasitism on RMR (Kristan & Hammond 2000, 2003), but in contrast to work by Meagher & O’Connor (2001), which found that nematode infection resulted in increased metabolic rates in deer mice only under short‐term but severe cold stress (2 °C plus Heliox gas flow).…”
Section: Discussionsupporting
confidence: 92%
“…However, we did not detect an interactive effect of thermoregulation and pathogen infection on metabolic rate, indicating that the energetic costs of infection with M. gallisepticum are comparable at thermoneutral and subthermoneutral temperatures. Our results are consistent with previous work in endothermic rodents, which detected additive but not interactive effects of cold exposure and nematode parasitism on RMR (Kristan & Hammond 2000, 2003), but in contrast to work by Meagher & O’Connor (2001), which found that nematode infection resulted in increased metabolic rates in deer mice only under short‐term but severe cold stress (2 °C plus Heliox gas flow).…”
Section: Discussionsupporting
confidence: 92%
“…How else can we explain the fact that a difference as small as 10% (often less!) between the mean resting MR of two populations, groups, or treatments can be the subject of pages of discussion while variation as large as 200% in resting MR among individuals does not even merit mention (Meagher and O'Connor 2001, Thomas et al 2001, Mathias et al 2006, Scantlebury et al 2007)? Many comparative eco‐physiologists may implicitly assume that among‐individual variation in resting MR is simply noise that has the undesirable effect of obscuring an underlying ecological or evolutionary signal.…”
Section: Energy Metabolism: the Mystery Of Intra‐specific Variationmentioning
confidence: 99%
“…The intensity of parasite-mediated selection, the degree of genetic isolation between populations, and the historical duration of the host-parasite contact are all likely to play important roles in determining the precise evolutionary response of a given population to parasites, leading to the possible development of local adaptations. Thus, for example, Meagher and O'Connor (2001) found that populations of deer mice (Peromyscus maniculatus (Wagner, 1845)) exhibited different degrees of resistance to nematodes (Capillaria hepatica) depending on their geographic location and the length of their historical association with the parasite.…”
Section: Introductionmentioning
confidence: 98%